DEVELOPMENT OF THE IONIC LIQUID MODIFIED CHITOSAN-TRIPOLYPHOSPHATE MICROPARTICLES FOR CONTROLLING INSULIN RELEASE - SAFDAR, RIZWAN (2021)
The unstable Chitosan-Tripolyphosphate (CS-TPP) nanoparticles/microparticles (NPs/MPs) results in burst release of Insulin in hydrochloric acid (HCl), while partial or poor solubility of material limits drug release in phosphate buffer saline (PBS).